PENGEMBANGAN MODEL PEMBELAJARAN METODE KASUS BERBASIS PROYEK PADA MATA KULIAH SISTEM INFORMASI MANAJEMEN - Agunawan, Agunawan; Hidayat, Andi Ircham; Firman, Ahmad (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Participatory and cooperative classes are part of the key performance indicators that are mandatory for universities in their fulfillment. National higher education standards state that case studies and project-based learning can both be used for teaching. However, students at the Nobel Institute of Technology and Business Indonesia have not been given knowledge about how to think at a higher level and solve cases that occur in the world of work. Using the project-based case method, this study aims to create a learning model for the Management Information System (MIS) course in an effort to support the application of the learning outcomes-based curriculum (OBE). Research & Development (R&D) research methodology uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Instructional analysis of learning outcomes; Semester Learning Plan (RPS); Lecture Event Unit (SAP); Learning Implementation Plan (RPP); and textbooks are some of the outputs of this research through the project-based Case Method Learning Model (CMT).